Exploring potentialities and challenges of horizontal management: A mixed study of two software worker coops in Argentina - Estragó, Alfonso (REVESCO. Revista de Estudios Cooperativos, 2023)
The article focuses on the analysis of one of the least examined dimensions of worker cooperativism: management. Specifically, on the basis of a mixed field study with qualitative-quantitative triangulation, it attempts to provide new and deeper elements of analysis to elucidate the potential of more "horizontal" management models. Leaning on interviews and surveys carried out in two Argentinean worker cooperatives, dedicated to software production, the study confirms the sustainable functioning of a set of practices that depart from the pyramidal scheme, in favour of democratic and participative dynamics at all decision-making levels. This could point out to the path towards a management approach that -in contrast to the typical Weberian bureaucratic order- presents a fully cooperative identity essence, while maintaining the search for high standards of economic effectiveness and efficiency. However, the results for one of the cases analysed indicate that such a path is neither linear nor challenge-free: there is the risk of undesired informal hierarchies’ emergence, which, if not addressed, could threaten the necessary harmony for the fully horizontal management model’s consolidation.
Keywords: Worker cooperative; Horizontal management; Informal hierarchy; Mixed study; Software